Trade, environment and sustainable development : views from Sub-Saharan Africa and Latin America : a reader - Konz, Peider (International Centre for Trade and Sustainable Development GenevaCH, 2000)
Presents a unique collection of analytical, research, commentary and case study articles from African and Latin American authors on the hard issues in the debate on trade, environment and sustainable development. Responds to the need to better inform global priorities, and contributes to clarifying the relationship between trade liberalization, economic growth, poverty alleviation, and environmental degradation.